Psychometric analysis of the three item loneliness scale in the Czech Republic - Meier, Zdenek; Novak, Lukas; Helvich, Jakub; Licka, Patrik; Tavel, Peter (BMC psychology, 2025)
BACKGROUND: There is a growing importance of loneliness measurement through valid and reliable instruments. However, to establish valid and reliable measures, there is a need to explore their psychometric properties in different research settings and language environments. For this reason, this study aimed to validate the Three Item Loneliness Scale (TILS) in the Czech Republic within a Slavonic language environment. METHODS: A sample of Czech adults (n = 3236) was used consisting primarily of university students. We utilized Classical Test Theory to assess TILS internal consistency, temporal stability, and factor structure. Item Response Theory (IRT) was used to estimate Differential Item Functioning (DIF), the discrimination and difficulty of the TILS items and to estimate the measurement precision of the whole scale. Construct validity was explored through the Spearman correlation coefficient using personality traits, depression, and anxiety. RESULTS: The results showed satisfactory reliability and validity of the TILS in the Czech Republic. The scale's internal consistency and temporal stability were found to be satisfactory (Cronbach's α = 0.81, McDonald's ω = 0.82, ICC = 0.71). The parallel analysis supported the unidimensionality of the TILS. The IRT results indicated that the highest measurement precision was reached in individuals with lower and above-average levels of loneliness. Significant correlations between the TILS scores, anxiety, depression, and personality traits supported the construct validity of the scale. Although the DIF analysis identified statistically significant differences in responses to items TILS_2 and TILS_3 based on education level and employment status (with no significant differences observed for TILS_1), the effect sizes of these differences were small. This indicates that, despite statistical significance, the practical impact on the scale's validity across these groups is minimal. CONCLUSIONS: The validated TILS provides a reliable and valid tool for assessing loneliness in the Czech Republic. Its brevity makes it a practical option for researchers and clinicians seeking to measure loneliness time-efficiently. Future studies should explore how adding new items could increase the measurement precision of the TILS.
Keywords: Psychometrics; Young Adult; TILS; osamocení; Measurement; Male; mladý dospělý; Adolescent; Česká republika; Adult; dospělí; mužské pohlaví; deprese; Item response theory; Validation; Loneliness; reprodukovatelnost výsledků; průzkumy a dotazníky; Reproducibility of Results; mladiství; Psychometric Properties; Czech Republic; úzkost; lidé; ženské pohlaví; psychometrie; Humans; Female; Surveys and Questionnaires; Depression; lidé středního věku; Anxiety; Middle Aged